An Effective Strategy of Introducing Chirality to Achieve Multifunctionality in Rare‐Earth Double Perovskite Ferroelectrics. Issue 9 (5th July 2022) - Hu, Zhao‐Bo; Wang, Chang‐Feng; Sha, Tai‐Ting; Shi, Chao; Ye, Le; Ye, Heng‐Yun; Song, You; You, Yu‐Meng; Zhang, Yi
Abstract: The hybrid rare‐earth double perovskite (HREDP) system provides great convenience for the construction of multifunctional materials. However, suffering from the high symmetry of their intrinsic structure, HREDPs face the challenges in the realization and optimization of ferroelectric and piezoelectric properties. For the first time, after a systematic investigation of the chirality transformation principle, it is found that the introduction of chirality is an efficient strategy for the targeted construction of multifunctionality, which simultaneously increases the possibility of obtaining multiaxial ferroelectricity and ferroelasticity, and effectively realizes a large piezoelectric response. Moreover, chirality induced ferroelasticity will also achieve excellent magnetic or optical response driven by pressure‐sensitive. To verify the feasibility of the above ideas, by using rare‐earth ions (Ce 3+ ) and suitable chiral organic cations, a new HREDP, ( R ‐N‐methyl‐3‐hydroxylquinuclidinium)2 RbCe(NO3 )6 (R1) is successfully designed, in which ferroelasticity, multiaxial ferroelectricity, satisfactory piezoelectric response, and the pressure‐driven single‐ion magnetics switch are simultaneously achieved for the first time. This work shows that the induction of chirality and the HREDP system provide an effective strategy and ideal platform for the expansion and optimization of the functions in perovskite ferroelectrics. Abstract : Introducing chiral cations, a pressure‐responsive hybrid rare‐earth perovskites, ( R ‐N‐methyl‐3‐hydroxylquinuclidinium)2 RbCe(NO3 )6, is constructed. ( R ‐N‐methyl‐3‐hydroxylquinuclidinium)2 RbCe(NO3 )6 exhibits satisfactory piezoelectric properties when combined with multiaxial ferroelectricity and ferroelasticity, with a piezoelectric charge constant of 104 pC N –1 and piezoelectric voltage constant of 420 × 10 −3  V m N −1 . Furthermore, the presence of ferroelasticity, allied with single‐ion magnetics (SIMs) behavior, brings about piezomagnetic on/off switching.